Registration system reform, information environment, and market manipulation - Chen, Yangfa; Jiang, Ji; Liu, Jie; Liu, Xiao; Wu, Weili (Journal of Corporate Finance, 2025)
In 2019, Chinese stock market regulators launched a comprehensive reform of the IPO regulatory system, transitioning from the approval system to the registration system. Using this reform as a quasi-natural experiment, we investigate the impact of IPO systems on market manipulation. We find that the registration system reform significantly inhibits market manipulation by improving the quality of firms’ information supply and reducing stock information asymmetry. In addition, our results indicate that the inhibitory effect of the registration system reform on market manipulation is more pronounced for firms with higher information exposure, greater information complexity, and a greater proportion of investors with better ability to interpret information. Further analyses show that the registration system reform also lowers trading values around manipulation events, and inhibits other types of trade-based manipulation and misconduct. This study sheds light on the crucial role of information transparency in financial markets’ effectiveness and investor protection.